Efficacy of acetazolamide and loop diuretics combinatorial therapy in congestive heart failure: A meta-analysis - Duta , Teuku F.; Zulfa , Putri O.; Alina, Meulu; Henira, Najlaika; Tsurayya, Ghina; Fakri, Fajar; Acharya, Yogesh (Narra X, 2024)
Acetazolamide, one of the carbonic anhydrase inhibitors, has been known to improve the efficacy of diuretic therapy in patients with in congestion heart failure. The aim this study was to investigate the effectiveness of acetazolamide when combined with loop diuretics in ameliorating diuresis and natriuresis in congestive heart failure using systematic review and meta-analysis. Randomized controlled trials (RCTs) and cohort studies were searched on PubMed, Scopus, and Embase on March 7, 2023, by using combinations of ‘acetazolamide’, ‘heart failure’ and along with their respective synonyms. The protocol had been registered on PROSPERO (CRD42023409864). The studies must investigate the effect of oral acetazolamide as the add-on to loop diuretic therapy to be included. Successful decongestion, natriuresis, and diuresis were set as the primary outcomes. The quality of the included studies was assessed using the Cochrane risk-of-bias tool for RCTs and Newcastle Ottawa Scale for observational studies. We identified 1176 titles in the initial search, and further reduced to five studies (three RCTs and two cohort studies) after in-depth screening. A total of 625 patients were recruited in the included studies published from 2015 to 2022. Results from meta-analysis revealed that acetazolamide and loop diuretics combination therapy ameliorated natriuresis (n=4; standardized means difference (SMD)=0.65; 95%CI: 0.07–1.24; p=0.03) and diuresis (n=2; SMD=0.29; 95%CI: 0.12–0.46; p=0.0009) when compared to loop diuretics alone. Acetazolamide and loop diuretics combinatorial therapy is efficacious in alleviating congestion in heart failure patients.